Changing trends of physicochemical parameters in Kaptai lake of Bangladesh (Research in Agriculture Livestock and Fisheries, 2015)
Physicochemical parameters were studied for a period of two years from July 2012 to June 2014. The parameters namely air and water temperature were estimated using centigrade thermometer, transparency using secchi disc while pH, CO2, total hardness, total alkalinity, dissolved oxygen (DO) were estimated using HACH water test kit. The highest air and water temperature (31.52°C and 30.38°C) were recorded in September, 2013 whereas the lowest air and water temperature 21.04°C and 20.42°C were recorded in January, 2014. The pH of water was found to alkaline in nature (6.9 to 8.20). The maximum free CO2 value (7.81 mg/l) was recorded in February, 2014 and minimum (2.36 mg/l) in November, 2012.The value of total alkalinity was found to fluctuate from 51.9 mg/l in December 2012 to 90.68 mg/l in December 2013. Total hardness of lake water varied from 37.8 (August) to 47.3 (November) in 2012 and 55.17 (July) to 87.49 (February) in 2013-14 with regular trends in fluctuation. Mean secchi disc reading varied from 1.94±.57 m in 2012-13 and 2.02±0.40 m in 2013-14. Dissolved oxygen was found to vary from 6.10 (February) to 6.80 (November) during 2012, 3.90 (February) to 6.38 mg/l (July) during 2013 with a mean value of 6.4±1.51 and 5.74±0.68 mg/l. Water depth was found to fluctuate from 4.39 to 11.76 m with a mean value of 7.96± 2.56 m for one year study. The present research provides baseline information on changing trends of physicochemical parameters of Kaptai Lake which will facilitate sustainable management and conservation of this lake ecosystem.Res. Agric., Livest. Fish.2(2): 319-327, August 2015